The Two-Component System CopRS Maintains Subfemtomolar Levels of Free Copper in the Periplasm of Pseudomonas aeruginosa Using a Phosphatase-Based Mechanism - Novoa Aponte, Lorena (2020)
Two-component systems control periplasmic Cu1 homeostasis in Gramnegative bacteria. In characterized systems such as Escherichia coli CusRS, upon Cu1 binding to the periplasmic sensing region of CusS, a cytoplasmic phosphotransfer domain of the sensor phosphorylates the response regulator CusR. This drives the expression of efflux transporters, chaperones, and redox enzymes to ameliorate metal toxic effects. Here, we show that the Pseudomonas aeruginosa two-component sensor histidine kinase CopS exhibits a Cu-dependent phosphatase activity that maintains CopR in a nonphosphorylated state when the periplasmic Cu levels are below the activation threshold of CopS. Upon Cux+ binding to the sensor, the phosphatase activity is blocked and the phosphorylated CopR activates transcription of the CopRS regulon. Supporting the model, mutagenesis experiments revealed that the ΔcopS strain exhibits maximal expression of the CopRS regulon, lower intracellular Cux+ levels, and increased Cu tolerance compared to wild-type cells. The invariant phosphoacceptor residue Hisx235 of CopS was not required for the phosphatase activity itself but was necessary for its Cu dependency. To sense the metal, the periplasmic domain of CopS binds two Cux+ ions at its dimeric interface. Homology modeling of CopS based on CusS structure (four Agx+ binding sites) clearly supports the different binding stoichiometries in the two systems. Interestingly, CopS binds Cux+/2+ with 3×10x-14 M affinity, pointing to the absence of free (hydrated) Cux+/2+ in the periplasm.